Immobilizing photogenerated electrons from graphitic carbon nitride for an improved visible-light photocatalytic activity - Sun, Han (Sci Rep, 2016)
Reducing the recombination probability of photogenerated electrons and holes is pivotal in enhancing the photocatalytic ability of graphitic carbon nitride (g-C(3)N(4)). Speeding the departure of photogenerated electrons is the most commonly used method of achieving this. To the best of our knowledge, there is no report on suppressing the recombination of photogenerated electron–hole pairs by immobilizing the electrons with ester functional groups. Here, for the first time the mesoporous g-C(3)N(4) (mpg-C(3)N(4)) was integrated with polymethyl methacrylate, a polymer abundant in ester groups, which showed a photocatalytic activity unexpectedly higher than that of the original mpg-C(3)N(4) under visible-light irradiation. Experimental observations, along with theoretical calculations, clarified that the impressive photocatalytic ability of the as-modified mpg-C(3)N(4) was mainly derived from the immobilization of photogenerated electrons via an electron-gripping effect imposed by the ester groups in the polymethyl methacrylate. This novel strategy might also be applied in improving the photocatalytic performance of other semiconductors.